Changing Habits and Attitudes towards Smoking among Future Physicians - Tee, G.H.; Hairi, Noran Naqiah; Farizah, H.; Azhana, N.H. (Malaysian Medical Association, 2007)
This study was conducted to assess the future physicians' habits, knowledge and attitude towards smoking. These factors influence the credibility of future Malaysian physicians as advocators and treatment providers. A crosssectional study was carried out among medical students at the Medical Faculty, University of Malaya. Knowledge on smoking was evaluated on the total scores for knowledge questions, with one point and zero for each correct and incorrect answer respectively, to a maximum of six potential points. Attitude towards smoking was measured by summation of scores on attitude items; each item was scored from five points for "against smoking" and one point for "favourable to smoking". The possible score ranged from 10 to 50. The response rate was 79.4%. Prevalence of overall smokers was 4.4%. The mean knowledge score among smokers (4.30 ± 2.17) was significantly lower than non-smokers (5.19 ± 1.28). The mean attitude score was higher among non smokers (44.30 ± 6.54) than smokers (39.86 ± 10.93). The re ult from this study showed that smoking prevalence was lower compared to previous studies done in Malaysia.